2017
DOI: 10.3892/ol.2017.7536
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of CADM1 and CADM4 are associated with advanced stage breast cancer

Abstract: Abstract. Cell adhesion molecule (CADM) genes encode immunoglobulin superfamily molecules, which are involved in cell-cell adhesion in a number of human epithelia. Through the maintenance of epithelia, CADM genes protect against malignant conversion and metastasis. Whilst numerous in vitro studies have investigated the molecular characteristics of CADM1 and CADM4 and in vivo studies have investigated CADM1 and CADM4 expression in a number of tumor types, the roles of CADM1 and CADM4 have yet to be elucidated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 22 publications
1
24
1
Order By: Relevance
“…CADM1 is frequently lost in invasive lung adenocarcinoma lesions when compared with those non‑invasive lung adenocarcinoma lesions 5. In recent years, accumulated evidences have confirmed that CADM1 is always inactivated in breast cancer, and its inactivation closely associated with patients’ poor prognosis and advanced progression 68. For example, a study published by Saito et al8 reported that 76.9% (160/208) of primary invasive breast cancer tissues showed CADM1 negative expression, and lack of CADM1 expression in these cases was associated with advanced tumor stage, suggesting a vital role of CADM1 plays in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…CADM1 is frequently lost in invasive lung adenocarcinoma lesions when compared with those non‑invasive lung adenocarcinoma lesions 5. In recent years, accumulated evidences have confirmed that CADM1 is always inactivated in breast cancer, and its inactivation closely associated with patients’ poor prognosis and advanced progression 68. For example, a study published by Saito et al8 reported that 76.9% (160/208) of primary invasive breast cancer tissues showed CADM1 negative expression, and lack of CADM1 expression in these cases was associated with advanced tumor stage, suggesting a vital role of CADM1 plays in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…CADM1, a member of the cell adhesion molecule family, has been proven to be a tumor suppressor in many cancers, including breast cancer (15), esophageal squamous cell carcinoma (16), and hepatocellular carcinoma (17). In MM, it was reported that the expression of CADM1 was also significantly downregulated and functions as a tumor suppressor by suppressing matrix metalloproteinases (MMPs) in MM (18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is considered that CADM1 and CADM4 suppress tumor development in cases of breast cancer. However, we previously evaluated CADM1 and CADM4 expression in breast cancer and found that those expression levels were less frequently decreased in TNBC cases than in non-TNBC cases (20). In the present study, we investigated further into CADM1 and CADM4 expression levels in both CNB and surgical specimens in TNBC patients who received PST.…”
Section: Discussionmentioning
confidence: 99%
“…IHC staining for CADM1 and CADM4 was performed by same method as previously described (20). The breast cancer tissue samples were fixed in 10% formalin, embedded in paraffin, cut into 4-µm sections and stained with hematoxylin and eosin (H&E) and other primary antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation